2016
DOI: 10.1007/s00441-015-2343-0
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue cells expressing fibro/adipogenic progenitor markers increase under chronic damage: relevance in fibroblast-myofibroblast differentiation and skeletal muscle fibrosis

Abstract: Fibrosis occurs in skeletal muscle under various pathophysiological conditions such as Duchenne muscular dystrophy (DMD), a devastating disease characterized by fiber degeneration that results in progressive loss of muscle mass, weakness and increased extracellular matrix (ECM) accumulation. Fibrosis is also observed after skeletal muscle denervation and repeated cycles of damage followed by regeneration. The ECM is synthesized largely by fibroblasts in the muscle connective tissue under normal conditions. Myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
143
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(160 citation statements)
references
References 49 publications
14
143
1
Order By: Relevance
“…We previously showed that the number of FAPs is augmented in models of increased fibrosis [42]. Therefore, we evaluated their presence by western blot analyses using markers of activated FAPs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that the number of FAPs is augmented in models of increased fibrosis [42]. Therefore, we evaluated their presence by western blot analyses using markers of activated FAPs.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that the number of connective tissue cells expressing FAPs markers are increased in three different fibrotic models: mdx mice, BaCl 2 -induced chronic damage and sciatic nerve denervation [42], suggesting a role of these cells in fibrosis associated to skeletal muscle. It seems that FAPs cells are required for correct regeneration in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations